Plasma Lipids and Platelet Membrane Fluidity in Essential Hypertension - Quan Sang, Kim Hanh Le; Mazeaud, Madeleine; Astarie, Catherine; Duranthon, Véronique; Driss, Fathi; Devynck, Marie-Aude (Thrombosis and Haemostasis, 1993)
Essential hypertension is often associated with high levels of plasma cholesterol or triglycerides. The relationships between plasma lipids and platelet lipids, membrane fluidity and functions in untreated hypertensive patients were investigated by measuring the fluorescence anisotropies of two fluorescent dyes (DPH and its cationic derivative, TMA-DPH, with different subcellular localization), cytosolic Ca2+ and pH, cyclic AMP content and aggregation to ADP and collagen. Hypercholesterolemia was found to be accompanied by a rise in platelet cholesterol content without changes in TMA-DPH or DPH anisotropies whereas hypertriglyceridemia was associated with a decreased cholesterol to phospholipid molar ratio, a decreased DPH anisotropy and a tendency of the cytosol to alkalinize. These results point out the differences between the effects of an acute cholesterol load and those of chronic hypercholesterolemia on platelet membrane microviscosity and aggregation. They demonstrate a strong association between plasma triglyceride levels and platelet membrane structure.